Sentiment Analysis of Public Opinion in Indonesia on China's Belt Road Initiative - Anang Masduki; Panqiang Niu; Muhammad Hamka; Zalik Nuryana (Universitas Multimedia Nusantara, 2026)
This research wants to answer the growing public opinion in Indonesia about the Belt Road Initiative project. The data source used is social media twitter with content analysis as a research method. Twitter data from January 2016 to September 2021 is limited to the Indonesian language and Indonesian territory. From the results of data mining using Python with search keywords: